Secondary structure and X-ray crystallographic analysis of the Glideosome-Associated Connector (GAC) from Toxoplasma gondii - Matthews,S (Crystals, 2022)
A model for parasitic motility has been proposed in which parasite filamentous actin (F-actin) is attached to surface adhesins by a large component of the glideosome, known as the glideosome-associated connector protein (GAC). This large 286 kDa protein interacts at the cytoplasmic face of the plasma membrane with the phosphatidic acid-enriched inner leaflet and cytosolic tails of surface adhesins to connect them to the parasite actomyosin system. GAC is observed initially to the conoid at the apical pole and re-localised with the glideosome to the basal pole in gliding parasite. GAC presumably functions in force transmission to surface adhesins in the plasma membrane and not in force generation. Proper connection between F-actin and the adhesins is as important for motility and invasion as motor operation itself. This notion highlights the need for new structural information on GAC interactions, which has eluded the field since its discovery. We have obtained crystals that diffracted to 2.6–2.9 Å for full-length GAC from Toxoplasma gondii in native and selenomethionine-labelled forms. These crystals belong to space group P212121; cell dimensions are roughly a = 119 Å, b = 123 Å, c = 221 Å, α = 90°, β = 90° and γ = 90° with 1 molecule per asymmetric unit, suggesting a more compact conformation than previously proposed